El ámbito objetivo de aplicación de la Ley de Represión de la Competencia Desleal, con especial referencia a la llamada “Competencia Prohibida” - Zegarra Mulánovich, Álvaro (Pontificia Universidad Católica del Perú, 2017)
This paper analyses the definition that the Act on Suppression of Unfair Competition adopted by Legislative Decree 1044 makes of its own objective scope. The positive concept of “act of competition”, that is the centerpiece of such a definition, is examined first, to then focus on the concepts excluded from it, either explicitly or implicitly, in line with both national and comparative legislation and case law. Particular attention is given to the exclusions from the concept of “act of competition” grouped in the literature under the name of “forbidden competition”.

El trabajo analiza la delimitación que hace la Ley de Represión de la Competencia Desleal aprobada por Decreto Legislativo 1044 de su propio ámbito de aplicación objetivo.Se examina, en primer lugar, el concepto positivo de “acto de concurrencia” que constituye el eje de dicha delimitación, para, a continuación, centrar la atención en los conceptos excluidos de ella, tanto explícita como implícitamente, al hilo tanto de los textos legales como de la jurisprudencia nacionales y comparados. Se presta particular atención al conjunto de exclusiones de la noción de “acto de concurrencia” agrupados por la doctrina bajo el nombre de “competencia prohibida”.
The objective scope of the law of repression of unfair competition, with special reference to the “forbidden competition”
Keywords: Competencia desleal; Acto de concurrencia; Relación de competencia; Competencia prohibida; https://purl.org/pe-repo/ocde/ford#5.05.01